Coups and post-coup politics in South-East Asia and the Pacific: conceptual and comparative perspectives - Croissant, Aurel (Australian journal of international affairs, 2013)
The 2006 coups in Fiji and Thailand—as well as the 2012 incident in Papua New Guinea—have sent timely reminders that military coups remain a threat to vulnerable democracies in South-East Asia and the Pacific. This article explores the interplay between structural factors that can create coup risks, the ‘coup-proofing’ strategies of political leaders and the occurrence of military coups. While the article examines the region as a whole, it pays particular attention to Myanmar (Burma), Thailand, Indonesia, Fiji and Papua New Guinea. Borrowing from the work of Belkin and Schofer, it argues that the level of coup risk in each country can be assessed by analysing the extent of regime legitimacy, the strength of civil society and the frequency of military coups in the past. By combining this analysis with an evaluation of coup-proofing strategies, the study discusses likely scenarios for the five focus countries as far as the likelihood of coups or, alternatively, the establishment of stable civilian control is concerned.
Gesehen am 19.03.2021